Motion sensor‐acquired reachable workspace correlates with patient‐reported upper extremity activities of daily living (ADL) function in facioscapulohumeral dystrophy. Issue 2 (1st December 2020) - Hatch, Maya N.; Kurillo, Gregorij; Chan, Vicky; Han, Jay J.
Abstract: Background: This study examines the correlation, and clinical meaningfulness, between reachable workspace outcome and reported activities of daily living (ADL) function of individuals with facioscapulohumeral dystrophy (FSHD). Methods: Twenty‐one FSHD subjects with various disease severity (clinical severity scores 1‐4) underwent reachable workspace evaluation and completed the Quality of Life in Neurological Disorders (NeuroQoL) upper extremity questionnaire. Spearman and receiver operator curve analyses were performed. Results: Moderate correlation was found between NeuroQoL scores and total (ρ = 0.7609; P < .01), and upper‐quadrants relative surface areas (RSAs) (ρ = 0.6969; P < .01). Five specific items (ie, shirt on, shirt off, use spoon, pull on pants, pick‐up clothes) demonstrated even higher correlations with total (ρ = 0.8397; P < .01) and above shoulder (ρ = 0.8082; P < .01) RSAs. A total RSA cuffoff value of 0.70 would achieve 100% sensitivity and 94% specificity (area under the curve = 0.975). Conclusions: Reachable workspace values identify when individuals have difficulties performing ADLs at home. This information improves patient monitoring, and clinical decision making by enabling more timely recommendations for medications, assistive devices, or considerations for clinical trial enrollments.